Beyond the dichotomy: incarceration dosage and mental health - Porter, Lauren C. (Criminology, 2019)
The findings from a growing body of research reveal that incarceration is detrimental for both physical and mental health. Incarceration, however, is typically conceptualized and operationalized as a dichotomy; individuals either have, or have not, been incarcerated. Considering that incarceration can range from one day to several years, a dichotomous measure may be overlooking important variations across lengths of exposure. In addition, most inmates are incarcerated more than once. In this study, we help to fill this gap by examining the relationship between incarceration dosage, measured as time served and number of spells, and mental health among a sample of young adults from the National Longitudinal Study of Youth 1997. By using fixed‐effects modeling, we find that the number of spells and the months incarcerated are positively related to mental health symptoms and the likelihood of depression. The association, however, is contingent on whether a respondent is currently or formerly incarcerated. Among current inmates, more time served is expected to improve mental health and the number of spells is unrelated to either outcome.